Characterization of microbial functional diversity and bacterial community structure affected by fertiliser, soil and plant growth stages in aerobic rice - Ali Hassan, Nor Ayshah Alia (2020)
Aerobic rice was introduced to increase water use efficiency. The rhizosphere of aerobic rice differs from that of conventional flooded rice due to their habitat differences. Recognizing the importance of microorganism to ecosystem function, bacterial community in aerobic rice rhizosphere was studied as a fundamental step towards the improvement of aerobic rice. Inorganic fertiliser could affect the microbial functional diversity and bacterial community structure of rhizosphere microorganism, which play a vital role in plant growth and soil fertility. Hence, the aim of this study was to determine the effect of fertiliser and soil type on microbial functional diversity bacterial community in aerobic rice rhizosphere. To achieve this, a total of 3 specific objectives was conducted. The first objective is to assess the effect of fertiliser rate and soil type on microbial functional diversity and bacterial community structure. The second objective is to determine the influence of fertiliser and soil type on the bacterial community composition and nitrogen cycling functional potential in the rhizosphere of aerobic rice. The third objective for this study is to evaluate the effect of plant growth stages on the microbial community in the rhizosphere of aerobic rice. Aerobic rice variety MRIA 1 was chosen for this study. A total of 4 different fertiliser rate was selected and tested with 2 different soil types. Non-fertilised, 100 kg/ha, 200 kg/ha, and 400 kg/ha of NPK compound fertiliser were applied to peat and sandy clay loam soil. The soil properties tested for this study were pH, soil moisture, cation exchange capacity, soluble phosphorus, total carbon, total nitrogen, and mechanical analysis. Plant growth characteristic recorded were plant length, numbers of tillers per hill, panicle length and straw nitrogen concentration. Microbial functional diversity was characterized by assessing the microbial activity and community level physiological profile using Biolog plicon sequencing was used to determined bacterial community structure, bacterial community composition, and nitrogen cycling functional potential. RDP FunGene was used to predict the functional potential of bacterial communities. Aerobic culturable microbial abundance was agar, and starch casein agar was used to quantify the abundance of bacteria, nitrogen-fixing microbes, fungi, phosphate-solubilizing microbes and actinomycetes, respectively. For the plant growth stages, samples were taken during the tillering, booting, grain filling, and mature stage. Microbial community were estimated using physiological fingerprints and microbial culturable abundance. Although peat and sandy clay loam were impacted differently when applied with different fertiliser rate, microbial functional diversity responded positively for both soils. The distinct microbial evenness between peat and sandy clay loam suggested that microbial functional diversity is dependent on soil properties. Carboxylic acid and acetic acid as well as carbohydrates were sensitive carbon sources that create dissimilar metabolic function of rhizosphere bacterial community in aerobic rice. L-arginine, L-asparagine, L- - cyclodextrin, N- -d-lactose were good indicators for distinguishing rhizosphere that added with fertiliser. 16s amplicon sequencing analysis demonstrated that Alphaproteobacteria, Nitrospirae and Bacteroidetes were identified as critical phyla when fertiliser added in peat while Gammaproteobacteria was the crucial phylum in sandy clay loam. Acidobacteria-6 and Chloracidobacteria were positive indicator showing that excessive fertiliser was applied in both soils. The addition of all fertiliser rate tested influenced the bacterial community composition by shifting the communities. This was shown through the increase of abundance by Candidatus Nitrososphaera and the decrease of abundance by Dok59, Olivibacter, Thermomonas and Dactylosporangium in peat. The bacterial communities in the sandy clay loam were shifted and shown by the increase of Clostridia and Solirubrobacter. The changes in bacterial communities such as increase and decrease of type of genera were dependent on soil chemical and physical properties. Although, rhizosphere bacterial communities were different in peat and sandy clay loam, the function of the genera in the communities was the same after fertiliser was introduced. The selection of genera during the bacterial commun type particularly soil properties. Desulfovibrio was identified as a genus that presence only in nonfertilised rhizosphere and can be used as an indicator in natural rhizosphere. Chitinophaga, Desulfosporosinus, Geobacillus, Nannocystis, Nitrosovibrio, and Perlucidibaca were the genus that solely presence in fertilised rhizosphere and can be used as an indicator in fertilised rhizosphere. Genera that solely presence in the fertilised rhizosphere were mainly contributed to nitrogen cycling. The growth stage of aerobic rice has an effect on determining the response and composition of microbial community in soil. Microbial community in rhizosphere responded according to plant effect produced during plant development which is primarily determined by soil type. Soil type particularly the soil physical and chemical properties are important factors in shaping the microbial community by directly influencing the environment of rhizosphere. This study concluded that microbial functional diversity and bacterial community in aerobic rice rhizosphere were influenced by fertiliser, soil type and growth stage. The use of fertiliser in the recommended rate (200 kg/ha of NPK compound fertiliser) is suitable in maintaining the function of bacterial community and thus positively influence the growth of aerobic rice.